Implementation of the Formative Assessment Model in the Development of Mathematics Learning Evaluation at the Elementary Level - Kharunissa, Rahma (EduMatika: Jurnal MIPA, 2023)
This research discusses the implementation of formative evaluation instruments in developing mathematics learning evaluation at the elementary level. Formative evaluation is carried out to provide regular feedback to teachers and students, allowing for proactive improvements in understanding of mathematical concepts. Through analysis of evaluation needs, development instruments, teacher training, and trials in mathematics classes, this research achieved positive results. Significant increase in student understanding, positive responses from teachers and students, as well as more dynamic learning adaptation. The conclusion of this study provides an in-depth view of the contribution of formative evaluation in the context of mathematics education at the elementary level. The implications stimulate further thinking in efforts to improve the quality of mathematics learning evaluation.